Hubungan Tingkat Pengetahuan Kehamilan Di Usia Remaja Dengan Kesehatan Mental di Kabupaten Tegal - Wulandari, Rr. Catur Leny; Yunita Setiya Aryani; Arum Meiranny (Journal of Midwifery and Health Science of Sultan Agung, 2024)
Pregnancy among teenagers has quite high risks for their psychological condition and the maturity of their reproductive organs. One of the problems that can influence the incidence of teenage pregnancy is the level of knowledge of teenagers and their mental health conditions which are not prepared from the start. Lack of knowledge about sexuality will have a negative impact on the mother's mental health. Therefore, the aim of this research is to determine the relationship between knowledge of teenage pregnancy and mental health in Tegal Regency. This research method is quantitative research with a cross sectional approach, sampling using purposive sampling, namely using subjects as many as 73 cases of teenage pregnancy who met the inclusion criteria and were analyzed using univariate analysis and bivariate analysis using chi square analysis. The research results obtained were that there was no significant relationship between knowledge of teenage pregnancy and mental health, p-value 0.856 (α = <0.05). This research can be concluded that there is no significant relationship between the level of knowledge of teenage pregnancy and mental health.